Pinpointing the axial ligand effect on platinum single-atom-catalyst towards efficient alkaline hydrogen evolution reaction - Zhang, Tianyu; Jin, Jing; Chen, Junmei; Fang, Yingyan; Han, Xu; Chen, Jiayi; Li, Yaping; Wang, Yu; Liu, Junfeng; Wang, Lei (Nature communications, 2022)
Developing active single-atom-catalyst (SAC) for alkaline hydrogen evolution reaction (HER) is a promising solution to lower the green hydrogen cost. However, the correlations are not clear between the chemical environments around the active-sites and their desired catalytic activity. Here we study a group of SACs prepared by anchoring platinum atoms on NiFe-layered-double-hydroxide. While maintaining the homogeneity of the Pt-SACs, various axial ligands (−F, −Cl, −Br, −I, −OH) are employed via a facile irradiation-impregnation procedure, enabling us to discover definite chemical-environments/performance correlations. Owing to its high first-electron-affinity, chloride chelated Pt-SAC exhibits optimized bindings with hydrogen and hydroxide, which favor the sluggish water dissociation and further promote the alkaline HER. Specifically, it shows high mass-activity of 30.6 A mgPt −1 and turnover frequency of 30.3  H 2 s −1 at 100 mV overpotential, which are significantly higher than those of the state-of-the-art Pt-SACs and commercial Pt/C catalyst. Moreover, high energy efficiency of 80% is obtained for the alkaline water electrolyser assembled using the above catalyst under practical-relevant conditions. Establishing robust structure/performance correlations is critical for the development of single-atom-catalysts with improved activity. Here, the axial ligand on Pt single-atom-catalyst is precisely adjusted and studied, showing that the ligand’s first electron affinity is crucial for the catalysis.